Disease Features and Gastrointestinal Microbial Composition in Patients with Systemic Sclerosis from Two Independent Cohorts. Issue 5 (17th February 2022) - Andréasson, Kristofer; Lee, S. Melanie; Lagishetty, Venu; Wu, Meifang; Howlett, Natalie; English, James; Hesselstrand, Roger; Clements, Philip J.; Jacobs, Jonathan P.; Volkmann, Elizabeth R.
Abstract : Objective: The study objective was to examine alterations in gastrointestinal (GI) microbial composition in patients with systemic sclerosis (SSc) and to investigate the relationship between SSc features and GI microbiota using two independent, international cohorts. Methods: Prospective patients with SSc from Lund University (LU), Sweden, from the University of California, Los Angeles (UCLA), United States, and control subjects provided stool specimens for 16S ribosomal RNA sequencing. Alpha and beta diversity analyses were performed. Multivariate negative binomial models identified differentially abundant genera between groups. Results: Patients from LU with SSc (n = 106) with recent SSc diagnosis (median disease duration 2.0 years) had lower abundance of commensal genera (eg, Faecalibacterium ) and higher abundance of pathobiont genera (eg, Desulfovibrio ) than LU‐controls (n = 85). Patients from UCLA with SSc (n = 71) had a similar prevalence of females, a similar body mass index, and similar age but an increased disease duration (median 7.1 years) compared with patients from LU with SSc. Factors associated with beta diversity in patients with SSc from both LU and UCLA included disease duration ( P = 0.0016), interstitial lung disease ( P = 0.003), small intestinal bacterial overgrowth ( P = 0.002), and immunosuppression use ( P = 0.014). In multivariable analysis, the UCLA‐SSc cohort had higher abundance of specific pathobiont genera (eg, Streptococcus ) compared with the LU‐SSc cohort. Conclusion: Enrichments and depletions in certain microbial genera were observed in patients recently diagnosed with SSc, suggesting that dysbiosis is present in early SSc. Specific disease features were independently associated with fecal microbial composition in both cohorts. After controlling for these factors, the abundance of several pathobiont bacteria differed between the cohorts, suggesting that environmental factors, along with disease manifestations, should be considered in future SSc studies.